Humanities and artificial intelligence - Quiroz Ávila, Rubén (2023)
Artificial intelligence (AI) and its potential consequences have led many around the world, including the academic community, to contemplate. There are perspectives ranging from ethical effects to those that view this phenomenon as bringing about irreversible cultural impacts. Thus, there are two opposing sectors that scrutinize it, both in terms of its premises and possible conclusions. One sector argues that it should be considered primarily for its dramatic apocalyptic consequences, which question the very nature of humanity and its accepted evolution, as well as the parameters through which human life is understood and organized. On the other hand, another group maintains that it represents a significant natural opportunity to focus operational efforts on technology. Therefore, it is an imminent and necessary scenario in which humans would enhance their capabilities. This is an age-old debate that has arisen many times in communities that have been affected by dramatic changes in which technology has played a decisive role.